Enhancing neonatal sepsis outcomes: the role of ascorbic acid and thiamine as adjuvant therapies - Mangshetty, Roopa B.; Binjanwadgi, Apurva A.; Gaddamanugu, Gayathri S. (International Journal of Contemporary Pediatrics, 2024)
Background: Neonatal sepsis, a systemic infection affecting newborns under 28 days, remains a leading cause of global infant mortality and morbidity. It affects approximately 2.8% of live births and accounts for 18% of newborn deaths. Neonates are particularly vulnerable due to their immature immune systems. Current management primarily involves timely antibiotic therapy and supportive care. Emerging evidence suggests potential benefits of micronutrients like ascorbic acid (vitamin C) and thiamine in sepsis management, but research on their combined use in neonatal sepsis is limited. Methods: This randomized controlled trial was conducted over 18 months involving 120 neonates with sepsis. The intervention group (n=60) received intravenous ascorbic acid (100 mg/day) and thiamine (4 mg/kg/day) for 5 days along with antibiotics, while the control group (n=60) received antibiotics alone. Clinical parameters, duration of hospital stay, NICU stay, antibiotic usage, ventilator support, vasopressor support, laboratory tests, and outcomes were compared between the two groups. Results: The intervention group showed significantly shorter durations of antibiotic therapy (11.22 vs 13.06 days, p=0.035), NICU stay (7.73 vs 10.91 days, p=0.003), and total hospital stay (12.11 vs 14.55 days, p=0.013) compared to the control group. At discharge, the intervention group had lower C-reactive protein (19.04 vs 33.82, p=0.041) and serum lactate levels (2.55 vs 3.32, p=0.008). Conclusions: Supplementation of ascorbic acid and thiamine as adjunctive therapy in neonatal sepsis appears to have potential benefits in reducing the duration of hospital stay and NICU stay, and improving certain biochemical markers, without any safety concerns.